A Study of the Students’ Reading Competency in the Junior High School Based on the 2013 Curriculum - Arcana Yasa, I Putu Budi; Tantra, Dewa Komang; Suputra, Putu Eka Dambayana (International Journal of Language and Literature, 2023)
Students’ reading abilities were below of minimum mastery criteria. This study was conducted to describe and analyze the students’ reading competency at junior high school level. The significance was to design and develop reading modular instructions with explicit reading strategies. This study was designed quantitatively. The students’ reading competency was measured quantitatively using a reading competency test. The test consisted of 25 multiple choice items with four options. The obtained data were analyzed quantitatively in two steps, namely: descriptive and inferential analysis. The mean scores of the students’ reading competency based on the reading indicators. The research findings were the mean score of the students’ reading competency in class D was 63.20 and in class H was 36.80. The range score between class D and H was same for descriptive text.  However, for recount text, the score in class D was larger than class H. Comparing to class H, the score variability in class D was larger for descriptive text and lower for recount text. The EFL teachers are suggested to use the appropriate reading strategies and materials which can encourage the students for following fun reading activity in the classroom.